2004
DOI: 10.1165/rcmb.2003-0319oc
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Mitogenic Factor Has Antiapoptotic Action and Is Upregulated in the Developing Lung

Abstract: Hypoxia-induced mitogenic factor (HIMF), also called FIZZ1 or RELMalpha, was a newly found cytokine. Hypoxia caused robust HIMF induction in the lung, and HIMF has potent pulmonary vasoconstrictive, proliferative, and angiogenic properties. To investigate the role of HIMF in lung development, we determined its spatial and temporal expression. From embryonic day (E)16 to postnatal day (P)28, HIMF was strongly expressed in the cytoplasm of bronchial epithelial cells, type II cells, endothelial cells, and primiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 36 publications
(36 reference statements)
8
68
1
Order By: Relevance
“…HIF1␣ is the most widely expressed of the tightly regulated ␣-subunits, whereas HIF2␣ expression varies significantly among cell types; in the mature lung, HIF1␣ is expressed ubiquitously in tissues exposed to hypoxia, whereas HIF2␣ expression is restricted specifically to the ATII cells and vascular endothelium (39). Work in the lung has shown that HIF1␣ can drive hypoxia-induced apoptosis in ATII cells (11,18), whereas other studies have shown that HIF2␣ plays a critical role in regulating production of pulmonary surfactant (1), as well as roles in alveolar development (16) and promoting antiapoptosis pathways (38). Considerable cross-regulation between isoforms has been suggested; for example, HIF2␣ expression is abrogated in lung-targeted HIF1␣ knockouts, and HIF2␣ activation may be dependent on initial HIF1␣ signaling (15,32).…”
Section: Discussionmentioning
confidence: 99%
“…HIF1␣ is the most widely expressed of the tightly regulated ␣-subunits, whereas HIF2␣ expression varies significantly among cell types; in the mature lung, HIF1␣ is expressed ubiquitously in tissues exposed to hypoxia, whereas HIF2␣ expression is restricted specifically to the ATII cells and vascular endothelium (39). Work in the lung has shown that HIF1␣ can drive hypoxia-induced apoptosis in ATII cells (11,18), whereas other studies have shown that HIF2␣ plays a critical role in regulating production of pulmonary surfactant (1), as well as roles in alveolar development (16) and promoting antiapoptosis pathways (38). Considerable cross-regulation between isoforms has been suggested; for example, HIF2␣ expression is abrogated in lung-targeted HIF1␣ knockouts, and HIF2␣ activation may be dependent on initial HIF1␣ signaling (15,32).…”
Section: Discussionmentioning
confidence: 99%
“…Beside proliferative effects, HIMF was demonstrated to have angiogenic (subcutaneous mouse in vivo matrigel plug model) and vasoconstrictive properties in pulmonary artery [3]. In addition, HIMF was shown to play a role in lung development, by regulation of apoptosis and participation in alveolarization and lung maturation [9] and compensatory lung growth after pneumectomy [10]. Also, HIMF (FIZZ1) was shown to be strongly increased during allergic pulmonary inflammation [6].…”
Section: Discussionmentioning
confidence: 99%
“…There are three other rodent members of this gene family that are known as RELM-b/FIZZ2/ mXCP3, resistin/FIZZ3/mXCP4, and RELM-g/FIZZ4/mXCP1. We reported previously that HIMF expression is increased in the lungs of chronically hypoxic mice (15) and in the normal developing murine lung (21). We have also shown that HIMF introduced into murine lung induces angiogenesis and vascular thickening (22).…”
mentioning
confidence: 83%
“…Previous studies from our laboratory have shown that recombinant HIMF has mitogenic, angiogenic, and vasoconstrictive effects in lung (15), and that HIMF possesses an antiapoptotic function in cultured murine embryonic lungs (21). It also has been reported that HIMF plays a role in type 2 T helper cell (Th)-mediated inflammation.…”
Section: Clinical Relevancementioning
confidence: 99%